Optimization of Catalytic Distillation for the Synthesis of Dimethyl Carbonate by Response Surface Methodology. Issue 47 (14th December 2020) - Feng, Yuchen; Guo, Bao; Tang, Shixiong; Liu, Yida; Liu, Jidong; Lv, Jianhua
Abstract: Dimethyl carbonate (DMC) was synthesized from methanol and ethylene carbonate (EC) in a reactive distillation column by transesterification using different composite oxide catalysts. The catalysts were characterized by XRD, N2 adsorption‐ desorption, CO2 ‐TPD, and NH3 ‐TPD. The results show that the Zr−Al catalyst has the most strong base sites and weak acid sites compared with other catalysts. The synergistic effect of acid‐base sites makes it show excellent catalytic performance for DMC synthesis. The operation parameters including reflux ratio, feed molar ratio, liquid hourly space velocity (LHSV) and catalyst dosage were optimized by factorial design based on response surface methodology (RSM). The best optimization conditions was: reflux ratio=5.23 : 1, feed molar ratio=6.05 : 1, LHSV=0.48 h −1, catalyst dosage=119.04 ml, the relative error between measured value and predicted value is small, which indicated that the reliability of the optimized process is high. Abstract : Dimethyl carbonate (DMC) was synthesized from methanol and ethylene carbonate (EC) in a reactive distillation column by transesterification using different composite oxide catalysts. Various techniques have been used to study the physical and chemical properties of the catalyst. The Zr−Al catalyst exhibits excellent catalytic performance. The response surface method was used to study the influence of process conditions on the catalytic behavior. Use RSM method and fitting model for modeling and optimization process.